2021
DOI: 10.1029/2020gl091608
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of the Breakthrough Phase of the Attachment Process in a Natural Lightning Flash

Abstract: The attachment process in cloud-to-ground lightning flashes is a crucial process that eventually switch on the discharge route between the cloud and the ground, acting as a transition from the leader stage with a peak current of 1-2 kA to the return stroke stage with a peak current of several tens of kiloamperes (Pu et al., 2019; Rakov & Tran, 2019). In response to the downward leaders starting from the charged clouds, upward connecting leaders (UCLs) of the opposite polarity are initiated from the grounded ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 39 publications
2
16
3
Order By: Relevance
“…In three of these events (see Figure 2), luminous structures were observed inside the shrinking common streamer zones just before the return stroke frames. The luminous structures in Figures 2a and 2c features based on their appearance: the first one links the positive and negative leaders, similar to the weak luminous route linking the approaching leaders observed by Jiang et al (2021) in natural lightning, and the other is floating. Notably, luminous structures act as selected routes and eventually transformed into a part of the return stroke channel.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…In three of these events (see Figure 2), luminous structures were observed inside the shrinking common streamer zones just before the return stroke frames. The luminous structures in Figures 2a and 2c features based on their appearance: the first one links the positive and negative leaders, similar to the weak luminous route linking the approaching leaders observed by Jiang et al (2021) in natural lightning, and the other is floating. Notably, luminous structures act as selected routes and eventually transformed into a part of the return stroke channel.…”
Section: Discussionmentioning
confidence: 70%
“…Kostinskiy et al (2016), for the first time, reported the evolution of the common streamer zone in meter-scale sparks generated by artificial clouds of negatively charged water droplets and estimated the speeds of the positive and negative leaders within it. Jiang et al (2021) reported a weak Abstract High-speed video frames and discharge current records of 34 long laboratory sparks were examined. Two consecutive frames of the breakthrough phase, depicting the evolution of the common streamer zone, were obtained in five events, all presented in this study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…, leader connecting behavior (e.g., Lu et al, 2013Lu et al, , 2016, striking distance characteristics (e.g., Qi et al, 2021;Visacro et al, 2017b), and streamer zone structure (e.g., Jiang et al, 2021;Plaisir et al, 2023;Saba et al, 2022;Tran & Rakov, 2017).…”
mentioning
confidence: 99%